ANALYSIS OF THE EFFICIENCY OF THE IRAQI FINANCIAL MARKET: AN ECONOMETRIC STUDY OF WEAK-FORM EFFICIENCY FOR THE PERIOD (2015–2024) - Thar Saadoon Shnaishel; Qassim Mahal Herez (Scholars Digest Publishing, 2025)
In the current study, we seek to test whether the Iraqi financial market operates efficiently at a level of weak-form. We do this by analyzing the volatility of the ISX Main 60 index for the 2015-2024 span. The study utilised a panel methodology that included the Augmented Dickey-Fuller (henceforth ADF). This is to gauge how stationary or otherwise the time series is in addition to also employing tests to detect patterns and assess unpredictability. Findings from our study revealed that the daily returns series is stationary but also confirmed the presence of marked autocorrelation and a clear deviation from randomness. This tells us that returns can be partially predicted. In conclusion, the study found that the Iraqi financial market fails to display weak-form efficiency, and this means that it is feasible to achieve abnormal returns using strategies based on technical analysis and historical information. Important recommendations were also provided for investors and policymakers in order help develop Iraq’s capital markets.
Keywords: Market Efficiency Hypothesis, Returns, Iraqi Financial Market, Time Series, Forecasting.